Habermas and Rawls : disputing the political - Finlayson, James Gordon; Freyenhagen, Fabian (Routledge, 2011)
Habermas and Rawls are two heavyweights of social and political philosophy, and they are undoubtedly the two most written about (and widely read) authors in this field. However, there has not been much informed and interesting work on the points of intersection between their projects, partly because their work comes from different traditions-roughly the European tradition of social and political theory and the Anglo-American analytic tradition of political philosophy. In this volume, contributors re-examine the Habermas-Rawls dispute with an eye toward the ways in which the dispute can cast.
Keywords: Habermas, Jürgen.; Rawls, John, -- 1921-2002.; Habermas, Jürgen; Rawls, John, -- 1921-2002; Political science -- Philosophy.; POLITICAL SCIENCE -- History & Theory.; Political science -- Philosophy; Electronic book.